La “sustancia capaz de querer”: hacia una voluntad resolutiva en pleno derecho - Gaiada, María Griselda (2014)
Far from the intellectualist versions of God ́s will (extrinsic voluntariness), we will offer a description of the late model divine will (1710), based on the assumption that “the mechanism of volitional forces” represents the highest point of divine will emancipation, endowing it with an intrinsic voluntariness that turns it into fully resolutive.